Использование взаимодействия различных видов искусств на занятиях по развитию речи студентов-иностранцев - Верник, О.А.; Неловкина Берналь, Е.А. (Культура народов Причерноморья, 2013)
В статье рассмотрены возможности использования взаимодействия различных видов
искусств на занятиях по развитию речи студентов-иностранцев. Предложенный авторами статьи
подход способствует личностному развитию творческого воображения и творческого потенциала
студентов-иностранцев, позволяет расширить кругозор учащихся, органично осуществить процесс их
эстетического воспитания. В статье рассматривались возможности использования произведений А.С.
Пушкина в рамках заданного полихудожественного метода. У статті розглянуті можливості використання взаємодії різних видів мистецтв на
заняттях з розвитку мовлення студентів-іноземців. Запропонований авторами підхід сприяє
особистісному розвитку творчої уяви та творчого потенціалу студентів-іноземців, дозволяє
розширити світосприйняття учнів, органічно здійснити процес їх естетичного виховання. У статті
розглядалися можливості використання творів А.С. Пушкіна в рамках поліхудожнього методу. The possibilities of the use of the interaction of various forms of art in the classroom for the
development of speech foreign students. In the classroom, using the interaction of art to trace the inner
relationship of speech, sound, color, space, gesture. Researchers concerned with the development of polyart students (B.P.Yusov, TB Nedaynova, N.Y.Voloshina, O.Miroshnichenko, E.Isaeva, V.I.Leybson, Z.L.Smelkova,
E.Kolokoltsev, S.I.Safaryan, T.I.Suhova, V.A.Domansky and others) have pointed out that the most productive
are those classes where the student develops the imagination, there is an appeal to his memory. Proposed by the
authors approach contributes to the personal development of creative imagination and creativity of foreign
students can broaden the horizons of students, organically carry out the process of aesthetic education. The
possibility of use of the works of AS Pushkin polyart within a given method. So the prospects for further research
zaklyuchayutsya in bringing the works of other prominent authors of Russian literature - Lermontov, Tolstoy,
Fyodor Dostoevsky, IA Bunin and others/